2016
DOI: 10.1111/vru.12430
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography of the Equine Distal Limb: Exploratory Study

Abstract: Positron emission tomography (PET) is a highly sensitive, noninvasive imaging technique for quantifying biological functions of tissues. However, at the time of this study, PET imaging applications had not been reported in the horse. The aim of this exploratory study was to determine whether a portable high-resolution PET scanner could be used to image the equine distal limb. Images of the front feet and fetlocks of three research horses, with known lesions localized to the distal front limbs, were acquired un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
0
28
1
1
Order By: Relevance
“…Studies in humans and equines comparing MRI findings and various joint lesions with FDG PET‐CT imaging have found associations between higher FDG avidity and MRI cartilage loss, effusion, and synovitis within symptomatic painful joint cohorts . In our study, FDG PET did not detect eight lesions of elbow osteoarthritis due to medial coronoid disease in six dogs that were diagnosed based on CT.…”
Section: Discussioncontrasting
confidence: 60%
“…Studies in humans and equines comparing MRI findings and various joint lesions with FDG PET‐CT imaging have found associations between higher FDG avidity and MRI cartilage loss, effusion, and synovitis within symptomatic painful joint cohorts . In our study, FDG PET did not detect eight lesions of elbow osteoarthritis due to medial coronoid disease in six dogs that were diagnosed based on CT.…”
Section: Discussioncontrasting
confidence: 60%
“…An additional notable volumetric imaging modality that is receiving increasing attention as a developing technology for assessment of subchondral bone is positron emission computed tomography (PET). Recent work has demonstrated that PET is able to identify lesions that were not visible using other imaging modalities, and furthermore to distinguish between active and inactive lesions (48). As PET gains further justification, the potential applications for evaluation of subchondral bone injury will likely warrant further discussion.…”
Section: Principles Of Diagnosis and Diagnostic Imagingmentioning
confidence: 99%
“…Other adjunctive methods have been explored to overcome the insensitivity of soft tissue evaluation with CT: contrast-enhanced CT (CECT), positron emission tomography, spectral CT, phase contrast x-ray computed tomography and dual energy CT [49][50][51][52][53][54][55][56]. These methods improve upon and expand the physiological information usually limited with standard CT.…”
Section: Computed Tomographymentioning
confidence: 99%